Apoptotic and Anti-Angiogenic Effects of Benzimidazole Compounds: Relationship with Oxidative Stress Mediated Ischemia/Reperfusion Injury in Rat Hind Limb - Algul, Oztekin; Karabulut, Alper; Canacankatan, Necmiye; Gorur, Aysegul; Sucu, Nehir; Vezir, Ozden (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2012)
Ischemia/reperfusion (I/R)-induced injury is a pathophysiological process consisting of a complex cascade characterized by an increase in reactive oxygen species production, pro-inflammatory cytokine release, and activated endothelial cells leading to cell damage and death. The aim of this study was to investigate effects of substituted 2- benzylbenzimidazole derivatives, 2-(3-methoxybenzyl)benzimidazole (BB3) and 2-(4-methoxybenzyl)benzimidazole (BB4), on I/R-induced changes in the markers of oxidative stress, apoptosis, and angiogenesis in rats. BB3 and BB4 were synthesized with microwave irradiation and conventional Phillips methods. I/R was performed by occlusion of femoral artery. Catalase activity and reduced gluthatione (GSH) levels as well as caspase-3, -8, and -9 activities were measured in muscle tissues as an index for oxidative stress and apoptosis, respectively. Vascular endothelial growth factor (VEGF) levels as an index for angiogenesis were also measured in the muscle tissues and sera. I/R decreased GSH levels, increased catalase activity and VEGF levels, and did not change caspase-3, -8, and -9 activities compared to control groups. BB3 and BB4 caused a further decrease in GSH levels and increased caspase-3, -8, and -9 activities in I/R group. These compounds caused a further increase in catalase activity and prevented the increase in VEGF levels induced by I/R. These data suggest that BB3 and BB4 exhibit apoptotic and anti-angiogenic activity with pro-oxidative effects resulting in oxidative stress in pathophysiological process of I/R-induced hind limb injury in rats.
Keywords: ischemia